Mathematical model for prediction of apparent viscosity of molasses - Togrul, H; Arslan, N (Elsevier Sci Ltd, 2004)
The rheological properties of molasses with or without added ethanol were studied using a rotational viscometer at several temperatures (45-60 degreesC), different amounts of added ethanol in molasses-ethanol mixture per 100 g of molasses (1-5%) and rotational speed ranging from 4.8 to 60 rpm. Flow behaviour index of less than one confirmed pseudoplasticity (n = 0.756-0.970). The power law model was found to be the appropriate to fit the flow curves of molasses. The consistency coefficient decreased with the amounts of added ethanol, while the flow behaviour index increased with the amounts of added ethanol. The consistency coefficient decreased with temperature but no harmonious variation was observed in the flow behaviour index values with increase in temperature. The apparent viscosity decreased with increasing temperature and shear rate, implying that molasses with or without added ethanol studied behaved as shear thinning. The mathematical models were developed for determining the apparent viscosity of molasses as affected by temperature and added ethanol. The suitability of the models relating the apparent viscosity were judged by using various statistical parameters such as the mean percentage error, the mean bias error, the root mean square error, the modelling efficiency and chi-square (chi(2)). (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: sugar beet pulp; molasses; ethanol; apparent viscosity